1978
DOI: 10.2503/jjshs.47.195
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Some Plant Growth Regulators on the Development of Strawberry Fruits in vitro Culture

Abstract: Fruits of strawberry, Fragaria x ananassa (Duch), cv. `Hohkoh-wase', one day prior to anthesis, were cultured in vitro to determine the roles of seeds in fruit development in relation to plant growth regulators .1. Fruits from which carpels were removed enlarged normally as intact fruits with carpels on the medium with a-naphthaleneacetamide (NAAm) . The ripening of intact fruits with carpels on the NAAm medium was suppressed in comparison to that of fruits without carpels.2. When fruits with or without carpel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…White fruits with achenes were allowed to ripe for three days, they were then deachened and used as controls. The color development was faster in deachened fruits than it was in the respective controls, in agreement with the observations of previous authors (Given et al 1988a;Kano and Asahira 1978). After doing the extraction and electrophoresis stages as described under Materials and Methods, the presence of the above-mentioned protein was detected in all fruits, so its presence is independent of the achenes.…”
Section: Fig 2 (A) Nondenaturing Electrophoresis (Page) Of Fruit Exsupporting
confidence: 91%
“…White fruits with achenes were allowed to ripe for three days, they were then deachened and used as controls. The color development was faster in deachened fruits than it was in the respective controls, in agreement with the observations of previous authors (Given et al 1988a;Kano and Asahira 1978). After doing the extraction and electrophoresis stages as described under Materials and Methods, the presence of the above-mentioned protein was detected in all fruits, so its presence is independent of the achenes.…”
Section: Fig 2 (A) Nondenaturing Electrophoresis (Page) Of Fruit Exsupporting
confidence: 91%
“…Leopold and Scott (1952) found that many other organic and inorganic compounds increased fruit set of excised tomato ovaries too, although no data on development of fruits after setting were given. However, in all cases an exogenous hormone was also necessary for the unpollinated ovaries to grow (Nitsch 1951, Leopold and Scott 1952, Peterson 1974, Kano and Asahira 1978. In the case of pea, the induction of fruit set and development by sucrose alone were counteracted by AMO-1618 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of tomato, limited parthenocarpic growth was achieved by adding synthetic auxins to the medium. The procedures of Nitsch, particularly the agar media, have been used to investigate the role of nutrients (Leopold andScott 1952, Jong et al 1974) and hormones , Peterson 1974, Kano and Asahira 1978 in the development of the ovary. The production of gibberellin (Baldev et al 1965) and cytokinin (Van Staden and Button 1978) in seeds has been studied in cultured excised pea pods.…”
mentioning
confidence: 99%
“…In general, auxins, cytokinins (CK), gibberellins (GA) plays a role in inhibiting maturation, while abscisic acid (ABA) is thought to play a role in promoting maturation (Leopold and Kriedemann, 1964). In the application study of in vitro culture of strawberry fruits, auxin and cytokinin inhibited maturation and GA promoted maturation in growing fruits (Kano and Asahira, 1978). In ripening fruits, ABA promoted ripening and CK suppressed ripening (Kano and Asahira, 1981).…”
Section: Introductionmentioning
confidence: 99%